Dnevna otroška bolnišnica - da otrok ne bi bolelo - Petrovič, Milinka (Slovenska pediatrija, 2010)
The following article deals with children hospitalized in the daily hospital of our ward. It describes the organizational structure of the Department of Paediatric Surgery and Intensive Care of the Division of Surgery, University Medical Centre Ljubljana. The plan for the nursing care concerning pain management and the participation of parents in pain management is outlined. The ultimate goal of parental involvement in the estimation of the degree of pain is pain reduction. According to our findings parental involvement can lead to reduction of the time during wich the patient experiences pain.
Keywords: Bolečina; Bolečina, merjenje; bolnišnično zdravljenje; Child; Day Care; Dnevna oskrba; Drug Therapy; Nursing; otroci; Otrok; Pain; Pain Measurement; Pooperativno obdobje; Postoperative Period; zdravstvena nega